Growth and Development of Digitaria insularis Biotypes Susceptible and Resistant to Glyphosate - PEREIRA,,G.R. (2017)
ABSTRACT The study aimed to evaluate the growth and development of biotypes of Digitaria insularis susceptible and resistant to glyphosate. Samples of biotypes were collected in Western Paraná in Cascavel, one susceptible (24o57'29.06" S and 53o30'23.73" W) and one resistant (24o54'54.99" S and 53o30'08.55" W; with Resistance Factor of 2.96). The experiment was arranged in a completely randomized design with four replications. The treatments consisted of different plant collection timings, carried out at regular intervals of 14, 21, 28, 35, 42, 49, 56, 63, 70, 77, 84, 91, 98, 105 and 112 days after emergence. The growth curve of susceptible and resistant biotypes were similar; however, the susceptible biotypes accumulated more leaf dry mass, while the resistant one accumulated more root dry mass. The resistant biotypes exhibited greater competitive efficiency and produced fewer tillers and inflorescences. The resistant biotype of D. insularis would have advantages over the original population of susceptible biotypes in an environment without application of glyphosate due to the low potential of aboveground biomass production and reproduction.